dnicholson/gas_toolbox: bug fix, new params added - Cara Manning (Zenodo, 2017)
This release includes several new parameterizations [Borges et al., 2004; Ito et al., 2011; Nicholson et al., 2016]. Relative humidity if not specified, now defaults to 100% rather than 80%. This was chosen to represent RH conditions at the surface interface, rather than at 10m (Thanks Roberta Hamme, and Cara Manning for discussion). A bug was discovered in Liang et al. 2013 param. Air density was corrected from rhoa = 1 to whoa = 1.225. Thank you to Mitch Wolf and Roberta Hamme @. UVic for finding this error. REFS: Borges, A. V., B. Delille, L.-S. Schiettecatte, F. Gazeau, G. Abril, and M. Frankignoulle (2004), Gas transfer velocities of CO2 in three European estuaries (Randers Fjord, Scheldt, and Thames), Limnol. Oceanogr., 49(5), 1630–1641, doi:10.4319/lo.2004.49.5.1630. Ito, T., R. C. Hamme, and S. Emerson (2011), Temporal and spatial variability of noble gas tracers in the North Pacific, J. Geophys. Res. Oceans, 116(C8), C08039, doi:10.1029/2010JC006828. Nicholson, D. P., S. Khatiwala, and P. Heimbach (2016), Noble gas tracers of ventilation during deep-water formation in the Weddell Sea, IOP Conf. Ser. Earth Environ. Sci., 35(1), 12019, doi:10.1088/1755-1315/35/1/012019.